Education and Health: The Role of Cognitive Ability - Govert Bijwaard; Hans van Kippersluis; Justus Veenman (Institute for the Study of Labor (IZA), 2013)
We aim to disentangle the relative contributions of (i) cognitive ability, and (ii) education on health and mortality using a structural equation model suggested by Conti et al. (2010). We extend their model by allowing for a duration dependent variable, and an ordinal educational variable. Data come from a Dutch cohort born between 1937 and 1941, including detailed measures of cognitive ability and family background at age 12. The data are subsequently linked to the mortality register 1995-2011, such that we observe mortality between ages 55 and 75. The results suggest that at least half of the unconditional survival differences between educational groups are due to a 'selection effect', primarily on basis of cognitive ability. Conditional survival differences across those having finished just primary school and those entering secondary education are still substantial, and amount to a 4 years gain in life expectancy, on average.
Keywords: C41; I14; I24; 330; education; cognitive ability; mortality; structural equation model; duration model